Microwave-Promoted Efficient Synthesis of Benzo[h]quinolines by Solvent-Free Three-Component Imino-Diels–Alder Reaction under One-Pot Conditions - Sarmah, Manas M.; Bhuyan, Debajyoti; Prajapati, Dipak (Synlett, 2013)
An one-pot, solvent-free imino Diels–Alder reaction has been developed under microwave conditions using 1-naphthylamine, aldehydes, and electron-deficient terminal alkynes in the presence of a catalytic amount of In(OTf)3 for construction of benzo[h]quinoline derivatives in short reaction times. The method is clean and operationally simple.
Keywords: imino-Diels–Alder reaction; metal-catalyzed multicomponent reaction; microwave-assisted organic synthesis; benzo[h]quinolines